Effectivity Test Of Saga Tree Leaf Extract (Adeanthera pavonia) Toward The Growth Of Escherichia coli Bacteria - Julahir Hodmatua Siregar; Aulia Aulia; Saiful Batubara (BEST Journal (Biology Education, Sains and Technology), 2023)
Indonesia has a wealth of natural resources in the form of the biggest medicinal plants in the world, in which traditional medicine is more likely to be developed. One of the traditional plant which is often used as traditional medicine is the saga leaves (Adenanthera pavonina). From some literature it is known that saga leaves contain chemical compounds such as essential oils, alkaloids, and flavonoids as antibacterial, it also contain abrins which is highly toxic, even though saga leaves are widely used traditionally to cure various diseases. The aim of this research is to find out if the extract of saga tree leaves (Adenanthera Pavonina) have the antibacterial effectiveness against the growth of Escherichia coli with the concentration of 3.123%, 6.25%, 12.5%, 25%, 50%, 100%. The used sample of saga tree leaves (Adenanthera Pavonina) were obtained from around the Karya road, Medan Johor sub-district, North Sumatra province. Sample preparation was done by making thick extract with maceration method. Antibacterial effectiveness test was done with disc diffusion. Research result showed the extract of saga tree leaves (Adenanthera Pavonina) contains alkaloids, flavonoids, saponins, steroids, tannins, and abrins and has the power of effectiveness against the growth of Escherichia coli bacteria with the average area of inhibition zone : concentration 3.123%=5.2 mm, concentration 6.25%=5.5 mm, concentration 12.5%=6.1 mm, concentration 25%=7.3 mm, concentration 50%=8.8 mm, concentration 100%=10.8 mm. The extract of saga tree leaves (Adenanthera Pavonina) has effectiveness against the growth of Escherichia coli bacteria with strong category